The low molecular weight protein tyrosine phosphatase promotes adipogenesis and subcutaneous adipocyte hypertrophy. Issue 9 (21st February 2021) - Stanford, Stephanie M.; Collins, Meghan; Diaz, Michael A.; Holmes, Zachary J.; Gries, Paul; Bliss, Matthew R.; Lodi, Alessia; Zhang, Vida; Tiziani, Stefano; Bottini, Nunzio
Abstract: Obesity is a major contributing factor to the pathogenesis of Type 2 diabetes. Multiple human genetics studies suggest that high activity of the low molecular weight protein tyrosine phosphatase (LMPTP) promotes metabolic syndrome in obesity. We reported that LMPTP is a critical promoter of insulin resistance in obesity by regulating liver insulin receptor signaling and that inhibition of LMPTP reverses obesity‐associated diabetes in mice. Since LMPTP is expressed in adipose tissue but little is known about its function, here we examined the role of LMPTP in adipocyte biology. Using conditional knockout mice, we found that selective deletion of LMPTP in adipocytes impaired obesity‐induced subcutaneous adipocyte hypertrophy. We assessed the role of LMPTP in adipogenesis in vitro, and found that LMPTP deletion or knockdown substantially impaired differentiation of primary preadipocytes and 3T3‐L1 cells into adipocytes, respectively. Inhibition of LMPTP in 3T3‐L1 preadipocytes also reduced adipogenesis and expression of proadipogenic transcription factors peroxisome proliferator activated receptor gamma (PPARγ) and CCAAT/enhancer‐binding protein alpha. Inhibition of LMPTP increased basal phosphorylation of platelet‐derived growth factor receptor alpha (PDGFRα) on activation motif residue Y849 in 3T3‐L1, resulting in increased activation of the mitogen‐associated protein kinases p38 and c‐Jun N‐terminal kinase and increased PPARγ phosphorylation on inhibitory residue S82. Analysis of the metabolome of differentiating 3T3‐L1 cells suggested that LMPTP inhibition decreased cell glucose utilization while enhancing mitochondrial respiration and nucleotide synthesis. In summary, we report a novel role for LMPTP as a key driver of adipocyte differentiation via control of PDGFRα signaling. Graphical abstract: We propose low molecular weight protein tyrosine phosphatase promotes adipogenesis through inhibitory dephosphorylation of PDGFRα in preadipocytes, leading to reduced activation of MAP kinases p38/JNK. This results in activation of the pro‐adipogenic transcription factor PPARγ through reduced MAP kinase‐mediated phosphorylation on inhibitory residue S82. Activated PPARγ in turn promotes a transcriptional program that shifts the metabolic profile of preadipocytes to one that favors differentiation in response to pro‐adipogenic stimuli or obesity.